Ambulatory ST segment monitoring. Problems, pitfalls, solutions, and clinical application. Issue 4 (October 1980) - Balasubramanian, V; Lahiri, A; Green, H L; Stott, F D; Raftery, E B
Abstract : The introduction of frequency modulated recording systems for ambulatory electrocardiographic monitoring (Oxford Medilog mark 2 and Cardiodyne cassette recorders) prompted comparison with a conventional direct recording type of recorder (Oxford Medilog mark 1). The recordings obtained by the frequency modulated recorders were very much superior to those obtained by the direct recording type of recorder. The direct recording suffered from poor low frequency response, phase shift, and cable motions artefacts. Correction of these problems with careful attention to electrode application enabled stable graphs to be obtained over 24 hours. The clinical applications were explored by comparing the results of exercie tests with a computer assisted system with frequency modulated ambulatory monitoring in 30 patients. A range of ST deviations from pure ST depressions throughout 24 hours, pure ST elevation, and a combination of ST elevation and depression were seen, suggesting a spectrum of changes hitherto unsuspected in these patients. Painless ST changes were approximately twice as common as those associated with pain. These findings indicate a valuable role for ST segment monitoring in ischaemic heart disease, particularly with the availability of high fidelity modulated tracings which do not distort ST segments.